Propagación y cultivo del helecho Microgramma vacciniifolia - Leva, Paula Edit; Rubio, Esteban Julian; Stancanelli, Santiago; Karlanian, Monica; Silva, Silvia Bibiana (Universidad Nacional de Hurlingham, 2024)
Poster